Morellia Robineau-Desvoidy 1830 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Morellia Robineau-Desvoidy, 1830 Morellia Robineau-Desvoidy, 1830: 405. Type-species: Morellia agilis Robineau-Desvoidy, 1830 (= Musca hortorum Fallén, 1817), by designation of Townsend (1916: 8). Morellia aenescens Robineau-Desvoidy, 1830 Morellia aenescens Robineau-Desvoidy, 1830: 406. Type-locality: France, Saint-Sauveur. Syntypes, formerly in Robineau-Desvoidy collection, now destroyed (not MNHN). Siberian records: Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 232); south part of Tyumenskaya Oblast’, subtaiga (Veselkin, 1966: 787); Kurganskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 226); Tomsk (Wnukovsky, 1936: 123); near Biysk (Sychevskaya, 1978: 82); Respublika Altay (Sorokina, 2006b: 139); valley of River Yenisey, northern taiga: Turukhansk, Verkhneimbatskoe, Yarzevo, Vorogovo, Kureyka, Igarka (Sychevskaya, 1974: 129); Altay, Pribaykal’e and Respublika Sakha [Yakutiya] (Zimin, 1951: 211); Siberia (Zimin & El’berg, 1970: 592); West and East Siberia (Pont, 1986a: 94). General distribution: Throughout the Palaearctic Region, from Europe to Japan. Morellia asetosa Baranov, 1925 Morellia asetosa Baranov, 1925: 59. Type-locality: Serbia: Topčider, near Belgrade. Lectotype ♂, CNC (designated by Pont, 1980: 313). Morellia simplicissima Zimin, 1951: 221. Type-localities: Russia, many localities in West Siberia, East Siberia, Russian Far East and Kazakhstan. Syntypes 25♂ ♀, ZIN (Pont, 2004: 92–93), and 1♀, MZPW (seen). Siberian records: Kurganskaya, Omskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 227); Smolino near Chelyabinsk, Krasnoyarskiy Kray: Minusinsk, Novoselovo, Manskiy Rayon (Sorokino), Irkutskaya Oblast’: Listvyanka [as “Irkutskiy Okrug, Listvenichnoe” in the original], Respublika Sakha [Yakutiya]: Yakutsk, Namshoe, Khamurgan near upper River Aldan (Zimin, 1951: 221, syntype localities of simplicissima ); Kurganskaya Oblast’ (Veselkin, 1989: 11); Respublika Tyva (Tamarina & Khromova, 1980: 81); South Tyva, River Naryn-gol (Pridantseva, 1967: 828); Central Respublika Sakha [Yakutiya]: Yakutsk, Khomustakh nasleg (Sychevskaya, 1972: 154); Siberia (Zimin & El’berg, 1970: 592); West and East Siberia (Pont, 1986a: 94). General distribution: Throughout the Palaearctic Region, though sparsely in Europe. Morellia hortensia (Wiedemann, 1824) Musca hortensia Wiedemann, 1824: 49. Type-locality: Indonesia, Java. Lectotype ♂, ZMUC (designated by Pont, 1973: 221). Siberian records: Central Respublika Sakha [Yakutiya]: Yakutsk, Khomustakh nasleg (Sychevskaya, 1972: 148, identification queried); East Siberia (Pont, 1986a: 95, record queried). General distribution: Oriental, Australasian and Afrotropical Regions, reaching the Palaearctic in East Russia, the Korean Peninsula and China. Morellia hortorum (Fallén, 1817) Musca hortorum Fallén, 1817: 252. Type-locality: Sweden, probably Skåne province. Lectotype ♂, NHRS (designated by Pont, 1984b: 286). Siberian records: Urals (Hennig, 1964: 970); Yamalo-Nenezkiy AO: Labytnangi, Muzhi (Gagarin & Veselkin, 1987: 215); Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 231); Chelyabinskaya Oblast’, Troizkiy Rayon (Kutuzova, 1993: 74); south part of Tyumenskaya Oblast’, forest steppe, subtaiga and southern taiga (Veselkin, 1966: 787); Kurganskaya, Tomskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 227); Tomsk (Wnukowsky, 1936: 123); near Biysk and Altay Mts (Sychevskaya, 1978: 82); Respublika Altay (Sorokina, 2006b: 139); Khanty-Mansiyskiy AO: Berezovskiy Rayon, Berezovo [as “Berezov on the River Ob’” in the original], Tobol’sk and Krasnoyarsk (Zimin, 1951: 209); South Tyva, River Naryn-gol (Pridantseva, 1967: 828); Respublika Tyva (Tamarina & Khromova, 1980: 81); Siberia as far as Yakutsk (Zimin, 1951: 209; Zimin & El’berg, 1970: 593); Irkutskaya Oblast’: Listvyanka [as “vom Baikalsee beim Dorfe Listwenitschnaja” in the original] (Hennig, 1964: 970); Port Baykal near Irkutsk (Draber-Moṅko, 1966: 6); Central Respublika Sakha [Yakutiya]: Yakutsk, Khomustakh nasleg (Sychevskaya, 1972: 148); valley of River Yenisey, forest steppe: Krasnoyarskiy Kray (Minusinsk, Shushenskoe), Respublika Tyva (Kyzyl, Cherbi), taiga: Krasnoyarsk, Yeniseysk and northern taiga: Turukhansk, Verkhneimbatskoe, Yarzevo, Vorogovo, Kureyka, Igarka (Sychevskaya, 1974: 129); West and East Siberia (Pont, 1986a: 95). General distribution: Throughout the Palaearctic Region, and also the north-west of the Oriental Region. Morellia podagrica (Loew, 1857) Cyrtoneura podagrica Loew, 1857: 45. Type-localities: Austria, the Wiener Schneekoppe, Carinthian Alps and Vienna. Syntypes 4♂ 4♀, ZMHU, and 1♂ 1♀, MCZ (all in Pont & Werner, 2006: 84). Siberian records: Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 231); Tomskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 227); Respublika Altay (Sorokina, 2006b: 139); Respublika Sakha [Yakutiya]: Verchoyansk, Bagatay, Yakutsk, Khomustakh nasleg, Tommot (Sychevskaya, 1972: 148); valley of River Yenisey, forest steppe: Krasnoyarskiy Kray (Minusinsk, Shushenskoe), Respublika Tyva (Kyzyl, Cherbi), taiga: Krasnoyarsk, Yeniseysk and northern taiga: Turukhansk, Verkhneimbatskoe, Yarzevo, Vorogovo, Kureyka, Igarka (Sychevskaya, 1974: 129); Siberia (Zimin, 1951: 209; Zimin & El’berg, 1970: 593); West and East Siberia (Pont, 1986a: 96). General distribution: Holarctic Region; in the Palaearctic, from montane and northern Europe to north China. Morellia simplex (Loew, 1857) Cyrtoneura simplex Loew, 1857: 45. Type-localities: England, Germany, probably also Poland, Hungary, Italy south to Sicily, Greece (Athens & Rhodes), Turkey. Syntypes 5♂ 5♀, ZMHU, and 1♂ 1♀, MCZ (all in Pont & Werner, 2006: 97). Siberian records: Middle Urals, unknown in Siberia (Zimin, 1951: 219); Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 231); Chelyabinskaya Oblast’, Troizkiy Rayon (Kutuzova, 1993: 74); south part of Tyumenskaya Oblast’, forest steppe, subtaiga and southern taiga (Veselkin, 1966: 783); Kurganskaya Oblast’ (Veselkin, 1989: 11); Omskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 227); West Siberia (Pont, 1986a: 96). General distribution: Palaearctic Region, from Europe east to China, also Pakistan. : Published as part of Sorokina, Vera S. & Pont, Adrian C., 2010, An annotated catalogue of the Muscidae (Diptera) of Siberia 2597, pp. 1-87 in Zootaxa 2597 (1) on pages 25-27, DOI: 10.11646/zootaxa.2597.1.1, http://zenodo.org/record/5318926 : {"references": ["Robineau-Desvoidy, A. J. B. (1830). Essai sur les myodaires. Memoires presentes par divers Savans a l'Academie Royale des Sciences de l'Institut de France, Sciences Mathematiques et Physiques, (2) 2, 813 pp. [Publication date 6 June; see also under Wiedemann, 1830.]", "Fallen, C. F. (1817) Beskrifning ofver de i Sverige funna fluge arter, som kunna foras till slagtet Musca. Forsta afdelningen. Kungliga svenska Vetenskapsakademiens Handlingar [3], 1816, 226 - 254.", "Townsend, C. H. T. (1916) Designations of muscoid genotypes, with new genera and species. Insecutor Inscitiae Menstruus, 4, 4 - 12.", "Zagrebin, A. I. (1987 a) On the fauna of pasture flies of the family Muscidae (Diptera) in the Urals. In: Cherepanov, A. I. (Ed.), Ecology and geography of arthropods in Siberia. Nauka (Siberian Division), Novosibirsk, pp. 231 - 233. [In Russian.]", "Veselkin, G. A. (1966) Flies (Diptera), satellites of domestic animals and man, in the southern part of the Tyumen' Region. Entomologicheskoe Obozrenie, 45, 779 - 792. [In Russian.] [English translation in Entomological Review, Washington, 45 (4), 439 - 447.]", "Sorokina, V. S. (2006 a) Distribution and ecology of house-flies (Diptera, Muscidae) in West Siberia. Euroasian Entomological Journal, 5, 221 - 233. [In Russian, with English abstract.]", "Sychevskaya, V. I. (1978) Synanthropic flies (Diptera) of Altay. Entomologicheskoe Obozrenie, 57, 81 - 85. [In Russian.] [English translation in Entomological Review, Washington, 57, 52 - 55.]", "Sorokina, V. S. (2006 b) Contributions to the knowledge of the house-flies (Diptera, Muscidae) of the mountain Altay. In: Materials of the meeting of Siberian and Far East entomologists \" The entomological research in Northern Asia \". Institute of Systematics and Ecology of Animals of Russian Academy of Sciences, Siberian Branch, Novosibirsk, pp. 138 - 140. [In Russian.]", "Sychevskaya, V. I. (1974) Synantropic flies from the valley of Enisey River. In: Kolomyiets, N. G. (Ed.), The Fauna and ecology of insects from Siberia. Akademiya Nauk SSSR, Novosibirsk, pp. 128 - 131. [In Russian.]", "Zimin, L. S. (1951) Insects, flies, volume 18 part 4. Family Muscidae, true flies (tribes Muscini, Stomoxydini). Fauna SSSR (n. s.), 45, 286 pp. Akademiya Nauk SSSR, Moscow and Leningrad [= St Petersburg]. [In Russian.]", "Zimin, L. S. & El'berg, K. Ya. (1970) Family Muscidae - true flies. In: Stackelberg, A. A. & Narchuk, E. P. (Eds), Keys to the insects of the European part of the USSR in five volumes (general editor G. Ya. Bey-Bienko). V (2). Diptera, Siphonaptera. Nauka, Leningrad [= St Petersburg], pp. 511 - 595. [In Russian.]", "Pont, A. C. (1986 a) Family Muscidae. In: Soos, A. & Papp, L. (Eds), Catalogue of Palaearctic Diptera. Volume 11. Scathophagidae - Hypodermatidae. Akademiai Kiado, Budapest, pp. 57 - 215.", "Baranov, N. (1925) Eine neue Morellia - Art aus Serbien. Encyclopedie Entomologique. (B II), Diptera, 2, 59 - 60.", "Pont, A. C. (1980) The identity of Morellia asetosa Baranov, 1925 (Diptera: Muscidae). Folia Entomologica Hungarica, 33, 313 - 316.", "Pont, A. C. (2004) Notes on types of Fanniidae and Muscidae (Diptera) in the Zoological Institute of the Russian Academy of Sciences, St Petersburg. International Journal of Dipterological Research, 15, 73 - 98.", "Veselkin, G. A. (1989) Specific structure and ecology of flies (Diptera, Cyclorrhapha) that are parasitic on domestic animals in the Kurgan area. In: Nikolaeva, N. V. (Ed.), Insects in the biogeocenozes of the Urals. Vsesoyuznoe entomologicheskoe obshchestvo Urala (Ural Division), Sverdlovsk [= Yekaterinburg], pp. 10 - 11. [In Russian.]", "Tamarina, N. A. & Khromova, L. A. (1980) Fauna and ecology of pasture flies (Diptera) - intermediate hosts of the parasitic nematodes in the Tuva Autonomous Republic. Entomologicheskoe Obozrenie, 59, 79 - 85. [In Russian, with English summary.] [English translation in Entomological Review, Washington, 61 (4), 141 - 147.]", "Pridantseva, E. A. (1967) The fauna of pasture flies (Diptera) connected with camels in South Tuva. Entomologicheskoe Obozrenie, 46, 827 - 834. [In Russian.] [English translation in Entomological Review, Washington, 46, 491 - 494.]", "Sychevskaya, V. I. (1972) On the synanthropic flies of Yakutiya. In: Ammosov, Yu. N. (Ed.), Fauna and ecology of the insects of Yakutiya. Akademiya Nauk SSSR, Yakutsk, pp. 144 - 157. [In Russian.]", "Wiedemann, C. R. W. (1824) Munus rectoris in Academia Christiana Albertina aditurus analecta entomologica ex Museo Regio Havniensi maxime congesta profert iconibusque illustrat. E regio typographeo scholarum, Kiliae [= Kiel], 60 pp.", "Pont, A. C. (1973) Studies on Australian Muscidae (Diptera). IV. A revision of the subfamilies Muscinae and Stomoxyinae. Australian Journal of Zoology, Supplementary Series, 21, 129 - 296.", "Pont, A. C. (1984 b) A revision of the Fanniidae and Muscidae (Diptera) described by Fallen. Entomologica Scandinavica, 15, 277 - 297.", "Hennig, W. (1964) Muscidae. [Part, Lieferung 248.] In: Lindner, E. (Ed.), Die Fliegen der palaearktischen Region, 63 b: 961 - 1008. Schweizerbart, Stuttgart.", "Gagarin, S. N. & Veselkin, G. A. (1987) Features of the fauna and ecology of zoophilous flies (Diptera) on farms of the large horned livestock in Yamalo-Nenetsk AO. In: Cherepanov, A. I. (Ed.), Ecology and geography of arthropods in Siberia. Nauka (Siberian Division), Novosibirsk, 214 - 215. [In Russian.]", "Kutuzova, T. M. (1993) Specific structure and dynamics of a number of flies in the forest-steppe of the Transurals connected with large horned livestock. In: Utochkin, A. S. (Ed.), Fauna and ecology of insects of the Urals. Perm State University, Perm, pp. 71 - 81. [In Russian.]", "Wnukowsky, W. (1936) Beitrage zur Insekten-Fauna des Bezirkes von Tomsk (West-Sibirien). Konowia, 15, 113 - 128.", "Draber-Mo nko, A. (1966) Bemerkungen zu den asiatischen Arten der Unterfamilie Muscinae (Diptera). Uwagi o azjatyckich gatunkach z podrodziny Muscinae (Diptera). Polskie Pismo Entomologiczne, 36, 3 - 15.", "Loew, H. (1857) Dipterologische Mittheilungen. IV. Cyrtoneura hortorum Wied. und die ihr verwandten europaischen Arten. Wiener entomologische Monatschrift, 1, 44 - 47.", "Pont, A. C. & Werner, D. (2006) The types of Fanniidae and Muscidae (Diptera) in the Museum fur Naturkunde, Humboldt-Universitat zu Berlin, Germany. Mitteilungen aus dem Museum fur Naturkunde in Berlin, Zoologische Reihe, 82, 3 - 139."]}